Innovations towards achieving environmentally sustainable operating theatres: A systematic review. Issue 3 (June 2023) - Perry, Helen; Reeves, Nicola; Ansell, James; Cornish, Julie; Torkington, Jared; Morris, Daniel S.; Brennan, Fiona; Horwood, James
Abstract: Introduction: The NHS accounts for 5.4% of the UK's total carbon footprint, with the perioperative environment being the most resource hungry aspect of the hospital. The aim of this systematic review was to assimilate the published studies concerning the sustainability of the perioperative environment, focussing on the impact of implemented interventions. Methods: A systematic review was performed using Pubmed, OVID, Embase, Cochrane database of systematic reviews and Medline. Original manuscripts describing interventions aimed at improving operating theatre environmental sustainability were included. Results: 675 abstracts were screened with 34 manuscripts included. Studies were divided into broad themes; recycling and waste management, waste reduction, reuse, reprocessing or life cycle analysis, energy and resource reduction and anaesthetic gases. This review summarises the interventions identified and their resulting effects on theatre sustainability. Discussion: This systematic review has identified simple, yet highly effective interventions across a variety of themes that can lead to improved environmental sustainability of surgical operating theatres. Combining these interventions will likely result in a synergistic improvement to the environmental impact of surgery. Highlights: Perioperative environments use 3–6 times more energy than the hospital in general. Paper/cardboard recycling bins in operating areas led to a 50–67% recycling rate. Reusable items can lead to 70% reduction in waste generation. Alcohol scrub solutions vs handwashing saves ∼930, 000 L/year/hospital of water. Dispensing propofol in 20 mL bottles instead of 50/100 mL reduces drug wastage by 90%.